2008
DOI: 10.1177/004908570803800304
|View full text |Cite
|
Sign up to set email alerts
|

Health care services in Punjab: Findings of a patient satisfaction survey

Abstract: Based on the primary data for 499 patients, 135 IPD and 364 OPD, in 62 hospitals across all the 20 districts in Punjab, the study discovered that contrary to the popular notion, the satisfaction level of the patients with the services delivered at hospitals managed by Punjab Health Systems Corporation (PHSC) was significantly high on most of the parameters. Both outdoor patients and indoor patients found the location of the hospitals accessible, diagnostic facilities in order, and quality of medical care satis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 6 publications
0
3
0
1
Order By: Relevance
“…In the present study, 67.2% of them reported that the distance from the nearest service provider as less than 5 km, whereas rest 31.7% reported being more than 5 km. While in a study done by Pawan Kumar Sharma et al (2008),[31] 40% of them has reported that the nearest health service provider with proximity from their place was less than 5 km and the rest 60% reported more than 5 km.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, 67.2% of them reported that the distance from the nearest service provider as less than 5 km, whereas rest 31.7% reported being more than 5 km. While in a study done by Pawan Kumar Sharma et al (2008),[31] 40% of them has reported that the nearest health service provider with proximity from their place was less than 5 km and the rest 60% reported more than 5 km.…”
Section: Discussionmentioning
confidence: 99%
“…2005). [19] In a study done by Pawan Kumar Sharma et al (2008),[31] the main reasons for selection of a particular hospital are inexpensive (87.9%) and skilled doctors (65.9%).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Patients" perceptions about healthcare systems seem to have been largely ignored by health care managers in developing countries. [4][5][6] Over the past 10 years consumer satisfaction has gained widespread recognition as a measure of quality in many public sector services. Patient satisfaction is now deemed an important outcome measure for health services; however, this professed utility rests on a number of implicit assumptions about the nature and meaning of expressions of "satisfaction".…”
Section: Introductionmentioning
confidence: 99%
“…La insatisfacción del paciente asociado a la mala calidad de atención no es un problema aislado perteneciente solo a países desarrollados sino que afecta a todo el mundo, un ejemplo de esto es la mala calidad de las unidades prestadoras de salud en México, en donde la higiene en los ambientes hospitalarios como las salas de hospitalización, áreas quirúrgicas y servicios higiénicos son un problema. Además de esto los procedimientos realizados en diversos hospitales y similares se realizan con un nivel de seguridad mínimo (3) .…”
Section: Situación a Nivel Continentalunclassified